Trabzon Ayasofya Camii’nin “Mülkiyet Hakkı” Üzerine Bir İnceleme - Çoruhlu, Yakup Emre; Demir, Osman (Vakıflar Genel Müdürlüğü, 2014)
Mülkiyeti mazbut Fatih Sultan Mehmet Vakfı’na yönetim ve temsili 5737 sayılı Vakıflar Kanunu ile Vakıflar Genel Müdürlüğü’ne (VGM) ait Trabzon Merkez Fatih Mahallesi’nde “çeşmesi olan bahçeli kargir cami” vasıflı, 6.951,75 m2 miktarlı vakıf taşınmaz, vakıf taşınmaz mallar kütüklerinde mazbut hayrat olarak tescillidir. Bu vakıf taşınmaz aynı zamanda 2863 sayılı Kültür ve Tabiat Varlıklarını Koruma Kanunu uyarınca “korunması gerekli kültür ve tabiat varlığı” olarak tescilli olup 1.derece arkeolojik sit alanında bulunmaktadır. Taşınmazı VII. Osmanlı Padişahı Fatih Sultan Mehmet’in Trabzon’u 1461 yılında fethetmesi ile kendi kurduğu vakfına alarak camiye dönüştürüp vakfettiği bilinmektedir. Uzun süre VGM rızası dışında müze olarak kullanılan bu taşınmazın vakıf hukukuna uygun olarak tekrar cami vasfında kullanımı tartışılmıştır. Bu çalışma kapsamında Cumhuriyet’ten sonra taşınmazın mülkiyet hakkı kavramı çerçevesindeki hukukî durumu ülkemizin de tanıdığı uluslararası beyanname, sözleşme ve protokoller ile Anayasa, Medeni Kanun, Vakıflar Kanunu, Kadastro Kanunu, Kültür ve Tabiat Varlıklarını Koruma Kanunu ve Gayrimenkul Kiraları Hakkında Kanun çerçevesinde irdelenerek, taşınmazın konu olduğu idarî kararlar ve yargı kararları da özetlenerek taşınmaz özelinde değerlendirmeler yapılacaktır.

Ayasofya Mosque as the property of The Foundation of Fatih Sultan Mehmet is administered and represented by General Directorate of Foundations (VGM) in Turkey, according to the Foundations Law numbered 5737. It is 6.951,75 m2 at Fatih District in Trabzon and registered as mazbut waqf on title deed “masonry mosque garden with fountain”. In addition, it is registered on title deed “cultural and natural property to be protected” and is in first-degree archaeological protected area according to Protection of Cultural and Natural Heritages Law numbered 2863. It is known that VIIth Ottoman Sultan, Fatih Sultan Mehmet conquered Trabzon in 1461. After the conquest, Fatih Sultan Mehmet converted Ayasofya into a mosque by including its own foundation. In a long time Ayasofya was used as a museum without permission of General Directorate of Foundations and usage of Ayasofya as a mosque has been discussed instead of a museum because of its status in accordance with the law of foundations. In this study, after establishment of Turkish Republic legal status of Ayasofya Mosque in terms of the concept of property rights will be investigated by examining the Universal Declaration of Human Rights, European Convention on Human Rights, The Constitution, Civil Law, Foundations Law, Cadastre Law, Protection of Cultural and Natural Heritages Law, Letting Law. Administrative decisions and adjudications will be summarized.
An Investigation on “Property Right” of the Trabzon Ayasofya Mosque
Keywords: Trabzon Ayasofya Cami; Mazbut Vakıf; Hayrat; Mülkiyet; Kullanım; Trabzon Ayasofya Mosque; Mazbut Waqf; Charity; Property; Usage